Ontologies, Information Science and Health Information Systems: articulations from a systematic review (Advances in Knowledge Representation, 2021)
The need for health care and the well-being of the population brings challenges to the management of information in health units. A current global challenge is the need to integrate electronic medical records systems, allowing continuous service to citizens and better use of both public and private resources. For continuous quality care, healthcare facilities need to access the various medical records of a patient, which are dispersed in different systems with different representations, at different times and in different geographic regions. The relationship between clinical terminologies, clinical information models and biomedical ontologies is then approached as a proposed solution for electronic patient records systems, however, it faces a gap between formal knowledge and epistemic knowledge of clinical practice. Therefore, a diagnosis of this scenario is proposed, carrying out a systematic review of the relationship between formal representation and informal language in clinical terminologies. Finally, it was noticed that little emphasis has been given to ontologies as a semantic support for the representation of knowledge at its ontological and epistemological levels, and that there is space and subsidies for Information Science to develop in this domain.